A sazonalidade da ocorrência de dengue no município de Campo Mourão - PR - Yokoo, Sandra Carbonera (2017)
Dengue is one of the most worrying arthropod-transmissible viral diseases at the present time, given the significant increase in cases, especially in the intertropical strip of the Earth and areas adjacent to the Tropic of Cancer and Capricorn lines. The transmission of the dengue virus has intensified due to the interconnection and circulation of people in the urban network, allowing the dispersion and, consequently, the increase of the cases. The research has as its theme: The seasonality of the occurrence of dengue in the municipality of Campo Mourão - PR. The temporal cut of the study covers the period from 2005 to 2013, and is linked to the Geography of Health. Through the scope of the subject studied, the analysis is multicausal and involves socio-environmental issues. The thesis aims to evaluate the distribution and temporality of confirmed cases of dengue, autochthonous and imported, and to characterize the occurrences according to climatic seasonality. Considering the period studied, there have been outbreaks of this disease since 2006; And in 2010 and 2013, more serious epidemics have occurred. The years studied were compared with the historical period of thirty years, 1986/2005, to verify if they presented themselves within the climatic normality. The methodology was based on the survey of the epidemiological records of dengue with the Health Department of the Municipality of Campo Mourão. From these surveys, tables, charts and maps were elaborated to understand the dispersion and geographical distribution of confirmed cases. Regarding the climatic approach, the data for the graphs and the rhythmic analysis were acquired from the database of the Campo Mourão / ECPCM Main Climatological Station and the National Institute of Meteorology / INMET. Subsequently, epidemiological information was correlated to meteorological data. There was follow up of the Endemic Control Program and the epidemiological team of the Municipal Health Department (LIRAa - Rapid Survey of Infestation Rates by Aedes aegypti), to identify breeding sites and evaluation of mosquito outbreaks. The distribution of dengue cases in the epidemic cycles studied was analyzed by mapping by proportional circles according to the census tracts (districts) of the municipality. The number of cases, the demographic density of each zone and the Incidence coefficient of dengue. The dengue research record was also analyzed for data on age, sex, occupation, schooling and referral of clinical cases of the population affected by the disease. Thus, some variables that influenced the epidemics of 2010 and 2013 in the municipality of Campo Mourão were evidenced, among which, the seasonality of dengue fever was confirmed, with cases expressivity in the summer and autumn seasons, with an autumn peak, in the Months of March / April / May, that is, with the influence of the period of intense rainfall, relative humidity of the high air and higher temperatures, favorable conditions to the ecology of the vector - Aedes aegypti. The winter season proved to be important in interrupting or minimizing the disease cycle, since it affects the development of the vector, mainly in relation to the occurrence of low temperatures, when they fall below the survival threshold of the vector. The way of life of the population also influences the increase of the cases, especially regarding the creation of small water collections formed by rainwater in irregularly discarded materials, in the gutters, in pots, among other utensils, confirming that the majority of the cases occurs in domiciles Or peridomestic; Thus, the sometimes precarious urban infrastructure and the inadequate disposal of solid waste in the urban environment facilitating the full development of the vector and its dispersion. Therefore, it is proven that the disease must be studied under a multi-causal approach. In the face of such evidence, it is evident the need for good land management, with planning actions in all spheres, both administrative areas of the municipality and the state of Paraná, as well as society, aimed at controlling dengue in Campo Mourão.